The Role of AI Chatgpt in Improving Writing Skills of Indonesian EFL Senior High School Students - Haziz, M. Zul; Agustina, Yulia; Arfah, Hajriana; Nazri, M. Adib (Universitas Pahlawan Tuanku Tambusai, 2025)
This study examined the effectiveness of AI ChatGPT in enhancing writing skills among Indonesian EFL learners at MA NWDI Tembeng Putik. A qualitative case study was conducted with 30 senior high school students using questionnaires and semi-structured interviews. The findings indicate that students benefited from ChatGPT in three main areas: improving grammar accuracy, strengthening coherence in essay organization, and supporting autonomous revision. Many students also reported that ChatGPT provided useful prompts when they faced difficulties generating ideas, although its impact on writing confidence was more limited. These results suggest that ChatGPT can serve as a valuable supplementary tool for EFL writing instruction, particularly in resource-limited classrooms. However, the study emphasizes the need for teacher guidance to ensure that AI use fosters critical thinking and responsible learning practices.